MEMBANGUN IMAN ANAK MUDA DI TENGAH TANTANGAN KEMAJUAN TEKNOLOGI (STUDI TERHADAP BUKU TEOLOGI DAN TEKNOLOGI MODERN KARYA HAROLD VICTOR L) - Adolfina Putnarubun; Heri Engel Solissa; Tia Metanfanuan; Almendo Kereuway; Chelsea Gabrella Sani; Bentelina Rut Fiay (Nusantara Hasana Journal, 2025)
The development and advancement of modern technology have had a significant impact on various aspects of human life, including the faith of young people. Young people living in the digital era are overwhelmed by the flow of information, social media, and technological advancements that influence how they think, behave, and develop their identities, including their faith identity. This study aims to analyze how young people's faith can be built and maintained amidst the challenges of technological advancement by examining the thoughts of Harold Victor L. in his book *Theology and Modern Technology*. The research method used is a qualitative approach with a literature review. The results show that technological advancement is neutral and can be a means of strengthening the faith of believers when used wisely and based on theological values. Therefore, faith formation for young people needs to integrate technological literacy, contextual theological education, and strengthening faith communities that are relevant to current developments.